2003
DOI: 10.1051/rnd:2003006
|View full text |Cite
|
Sign up to set email alerts
|

The incorporation of solubilized wheat proteins in milk replacers for veal calves: effects on growth performance and muscle oxidative capacity

Abstract: -Replacement of skim milk proteins by solubilized wheat protein (SWP) in milk replacers for veal calves would contribute to the reduction in feeding costs. The occurrence of metabolic disorders has, however, been reported. Forty-two male calves received one of three treatments over 140 days: a control diet, a diet containing SWP without or with branched-chain amino acid supplementation. Liveweight gain, carcass yield, color and conformation did not show any significant differences. No metabolic disorders were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 27 publications
(38 reference statements)
1
17
1
Order By: Relevance
“…The main contribution of this work was to mathematically determine how age-related changes in these metabolic pathways related to lipogenesis or nutrient catabolism, and in some indicators of tissue potential for circulating TG hydrolysis and nutrient transport, readily accounted for muscle fat accretion. This was achieved by finding combinations between plasma concentrations and several tissue traits, to produce a few numbers of trends representative of metabolic orientation [30]. Interestingly, the first three computed trends adequately described how profiles in plasma metabolites and overall FA metabolism in liver and WAT were associated, and thus argued for the validity of our mathematical approach.…”
Section: Discussionmentioning
confidence: 93%
“…The main contribution of this work was to mathematically determine how age-related changes in these metabolic pathways related to lipogenesis or nutrient catabolism, and in some indicators of tissue potential for circulating TG hydrolysis and nutrient transport, readily accounted for muscle fat accretion. This was achieved by finding combinations between plasma concentrations and several tissue traits, to produce a few numbers of trends representative of metabolic orientation [30]. Interestingly, the first three computed trends adequately described how profiles in plasma metabolites and overall FA metabolism in liver and WAT were associated, and thus argued for the validity of our mathematical approach.…”
Section: Discussionmentioning
confidence: 93%
“…In addition, when they supplemented branched-chain AA, no enhancement in growth performance was observed under the HWP diet (Ortigues-Marty et al, 2003). In that study, HWP replaced 50% of the milk proteins, whereas we only substituted 13%.…”
Section: Resultsmentioning
confidence: 64%
“…Feeding trials have shown that HWP can partially replace and perform as well as milk proteins in milk replacers. Ortigues-Marty et al (2003) observed no differences in live weight gain or carcass yield of male veal calves when HWP was substituted for 50% of the milk proteins in 22% CP milk replacers. However, these researchers used 4-wk-old calves, which are more capable of digesting various nonmilk proteins compared with newborns (Ternouth et al, 1976;Davis and Drackley, 1998;NRC, 2001).…”
Section: Introductionmentioning
confidence: 73%
“…As a consequence, the postprandial hormonal status is altered, thereby affecting protein metabolism: insulin secretion is lower with milk replacers rich in proteins which do not curdle in the abomasum (for review, see Hocquette and Bauchart, 1999). Furthermore, with a nonclotting diet, we observed an orientation of the muscle tissue towards a more oxidative type and indications of a lower efficiency of amino acids for protein deposition (Ortigues-Marty et al, 2003).…”
Section: Effect Of Nutrient Deliverymentioning
confidence: 88%